The protective effect of green tea on diabetes-induced hepato-renal pathological changes: a histological and biochemical study. (2nd January 2023) - Atia, Tarek; Sakr, Hader I.; Damanhory, Ahmed A.; Moawad, Karim; Alsawy, Moustfa
Abstract: We investigated the protective effect of green tea on diabetic hepato-renal complications. Thirty male Wistar rats were randomly divided into five equal groups: normal control, diabetic control, glibenclamide-treated, green tea-treated, and combined therapy-treated groups; ethical approval number "BERC-014-01-20." After eight weeks, animals were sacrificed by CO2 euthanasia method, liver and kidney tissues were processed and stained for pathological changes, and blood samples were collected for biochemical analysis. Diabetic rats showed multiple hepato-renal morphological and apoptotic changes associated with significantly increased some biochemical parameters, while serum albumin and HDL decreased significantly compared to normal control ( p  < .05). Monotherapy can induce significant improvements in pathological and biochemical changes but has not been able to achieve normal patterns. In conclusion, green tea alone has a poor hypoglycaemic effect but can reduce diabetic complications, whereas glibenclamide cannot prevent diabetic complications. The addition of green tea to oral hypoglycaemic therapy has shown a potent synergistic effect.